Rapid diagnosis of resistance to imidazolinone herbicides in barnyardgrass (Echinochloa crus-galli) and control of resistant biotypes with alternative herbicides - Matzenbacher,F.O. (2013)
The resistance of barnyardgrass (Echinochloa crus-galli) to imidazolinone herbicides is a worldwide problem in paddy fields. A rapid diagnosis is required for the selection of adequate prevention and control practices. The objectives of this study were to develop expedite bioassays to identify the resistance to imidazolinone herbicides in barnyardgrass and to evaluate the efficacy of alternative herbicides for the post-emergence control of resistant biotypes. Three experiments were conducted to develop methods for diagnosis of resistance to imazethapyr and imazapyr + imazapic in barnyardgrass at the seed, seedling and tiller stages, and to carry out a pot experiment to determine the efficacy of six herbicides applied at post-emergence in 13 biotypes of barnyardgrass resistant to imidazolinones. The seed soaking bioassay was not able to differentiate the resistant and susceptible biotypes. The resistance of barnyardgrass to imidazolinones was effectively discriminated in the seedlings and tiller bioassays seven days after incubation at the concentrations of 0.001 and 0.0001 mM, respectively, for both imazethapyr and imazapyr + imazapic. The biotypes identified as resistant to imidazolinones showed different patterns of susceptibility to penoxsulam, bispyribac-sodium and pyrazosulfuron-ethyl, and were all controlled with profoxydim and cyhalofop-butyl. The seedling and tiller bioassays are effective in the diagnosis of barnyardgrass resistance to imidazolinone herbicides, providing an on-season opportunity to identify the need to use alternative herbicides to be applied at post-emergence for the control of the resistant biotypes.